Performance enhancement of wireless sensor network by using non-orthogonal multiple access and sensor node selection schemes - Duy-Hung Ha; Duy-Binh Ha; Van-Truong Truong; Van-Duc Phan; Q. S. Vu (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In this paper, we investigate a relaying wireless sensor network (WSN) with the non-orthogonal multiple access (NOMA) and sensor node selection schemes over Rayleigh fading. Precisely, the system consists of two sensor clusters, a sink node, and an amplify-and-forward (AF) relay. These sensors applying the NOMA and sensor node selection schemes transmit the sensing data from the sensor clusters via the relay to the sink. We derived the expressions of outage probability and throughput for two sensor nodes. We also provide numerical results to examine the behavior of the system. Finally, we verify the validity of our analysis by using the Monte-Carlo simulation.